2001
DOI: 10.4049/jimmunol.166.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Enhancement by the HIV-1 Nef Protein

Abstract: The HIV-1 nef gene, essential for AIDS pathogenesis, encodes a 27-kDa protein (Nef) whose biochemical and biological functions are unclear. It has been suggested that Nef expression contributes to the T cell depletion observed during the disease by promoting their apoptosis. We report that in CD4+ human lymphoblastoid cell lines transfected with the nef cDNA obtained from three different HIV-1 strains, expression of the Nef protein enhances and accelerates the response to four unrelated apoptotic agents (staur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 58 publications
2
58
1
1
Order By: Relevance
“…However, T-cell priming for apoptosis is associated with the in vivo expression in both CD4 þ and CD8 þ T cells of the active forms of caspase-8 and caspase-3, 109 which can be induced in vitro by a number of HIV proteins, such as Tat, Env, Nef or Vpr. 62,49,71,63 Since T-cell activation is downmodulating the level of the apoptosis inhibitory protein FLIP (FLICE-like inhibitory protein), it was hypothesized that susceptibility of patients' T cells to AICD was associated with decreased c-FLIP expression. However, the levels of c-FLIP in purified CD4 þ and CD8 þ T cells from HIV þ donors do not differ from that of noninfected control donors.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
“…However, T-cell priming for apoptosis is associated with the in vivo expression in both CD4 þ and CD8 þ T cells of the active forms of caspase-8 and caspase-3, 109 which can be induced in vitro by a number of HIV proteins, such as Tat, Env, Nef or Vpr. 62,49,71,63 Since T-cell activation is downmodulating the level of the apoptosis inhibitory protein FLIP (FLICE-like inhibitory protein), it was hypothesized that susceptibility of patients' T cells to AICD was associated with decreased c-FLIP expression. However, the levels of c-FLIP in purified CD4 þ and CD8 þ T cells from HIV þ donors do not differ from that of noninfected control donors.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
“…[76][77][78] While our studies did not identify specific HIV-1 proteins that lead to activation of caspase-8 to initiate apoptosis when the LFA-1/ICAM-1 interaction is blocked, induction of caspase activity has been attributed to HIV-1 Env, protease, and the accessory proteins tat, nef, vpr, and vpu. [35][36][37][38]44,45,[79][80][81] Our data showed that X4 tropic and dual tropic viruses induced LFA-1-dependent resistance to apoptosis but not R5 tropic viruses. This result suggests that proteins specifically associated with X4/dual tropic viruses may be responsible for the phenomenon.…”
Section: Loss Of Lfa-1 Adhesion Inhibits Hiv Infectionmentioning
confidence: 85%
“…It has been shown that caspases 3, 6, 8, and 9 are activated by various HIV-1 proteins. [35][36][37][38][39][40][41][42][43][44][45] Thus, caspases may represent a link between integrins and HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 infection in tissue-culture conditions leads to syncytium formation and single cell lysis which are called cytopathic eff ects (Dedera and Ratner, 1991). Th ere are reports of the cytostatic or cytotoxic eff ects of HIV-1 proteins Tat, Vif, Vpr, Nef, and protease in cultured cells (Bartz and Emerman, 1999;Chen et al, 1999;Okada et al, 1997;Rasola et al, 2001). However, lysis of cultured T cells infected by HIV-1 and depletion of these cells in simian immunodeficiency virus infected monkeys has been observed without these viral proteins (Cao et al, 1996;McCloskey et al, 1997).…”
Section: Introductionmentioning
confidence: 99%